The The Influence of Perceived Usefulness, Perceived Easy of Use, and Perceived Value on Intention To Use E-Commerce - Syamillah, Fidelia; Sadat, Andi Muhammad; Berutu, Meta Bara (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This research looks into how the ideas of usefulness, ease of use, and value affect the desire of Generation Z to use online shopping sites. Information was gathered from online shoppers living in the Jabodetabek region by employing a quantitative approach through survey methods. The findings show that all three factors heavily influence the desire to use. Perceived1 Usefulness plays a key role in driving user intention, using a technology becomes more appealing to people when they see the advantages, such as saving time, easy transactions, and increased productivity. These advantages, as mentioned in the Technology Acceptance Model (TAM), have a significant impact on how likely people are to start using it. The way people see how easy it is to use something matters a lot. This means that if an online shopping site is simple to use, people are more likely to want to use it. This is especially true for younger people like those in Gen Z who grew up with technology. Furthermore, Perceived1 Value shows a strong influence on Intention1 to Use, indicating that users value platforms that offer not only convenience and functionality but also emotional and economic benefits. These findings emphasize the importance of designing e-commerce platforms that are not only useful and easy to use but also deliver a holistic and positive user experience.